Development of Android-Based Mobile Learning Media Using Smart App Creator to Improve Students' Multi-Representation Ability in Thermodynamic Materials - Pratiwi, Ildawati Febri; Novita, Nanda; Saifuddin, Saifuddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is a development research that aims to determine the feasibility, attractiveness, and convenience of android-based mobile learning application products on Thermodynamics material. As well as to find out the increase in the sustainability of multi-percentage of grade XI students in Thermodynamics material with the mobile learnig application in learning. This study uses a research and development (R&D) method with the Borg and Gall model. The methods carried out are tests and questionnaires. Based on the results of data analysis for the expert test, a percentage of 95% was obtained with the criteria of